An Analysis of the Surface Wind Data at Budiarto Airport by Using Wind Rose Method to Improve Cadets' Fly Safety - Nafi, Muhammad Aulia; Alfaridzi; W, Arsanto Noorwahyu (ENERGY: JURNAL ILMIAH ILMU-ILMU TEKNIK, 2023)
Wind conditions affect the stages of take-off, cruising, and landing in flight. To find out the wind conditions, it is necessary to analyze the surface winds, as well as at Budiarto Airport, which is the location of the flying training for several flight schools. One of them is the Politeknik Penerbangan Indonesia Curug (PPIC). For efficiency and optimalization of the flight training schedules and for the safety of flight cadets, this research is important to do. This study aims to determine the effect of surface winds at Budiarto Airport on flight training activities for PPIC cadets, to determine the ideal wind conditions for cadets' flight training activities  with solo and mutual phases, and to obtain the results of monthly surface wind trends analysis. For this reason, the wind rose method is used. This analytical descriptive study was conducted with stages of observation, problem formulation, data collection, data tabulation, and data processing. Data were collected by calculating and making tables of relative frequency of wind direction and speed. Data processing is done by making a diagram of the direction and speed of the wind using  the  wind  rose  method  with  the  help  of  the  WRPLOT  application.  The  result  is  that  the  surface  wind  at Budiarto  Airport  can be  categorized  as  safe  for  PPIC  cadet  flight  training.  The  wind  speed  with  the  highest percentage is wind with a speed below 10 knots (94.6%). The wind direction with the highest percentage is from 225°  to  255°  (13.15%).  The  recommended  time  for  solo  and  mutual  flight  training for  PPIC  cadets  is  April  to October.